Access to iodized salt in four areas of rural Papua New Guinea - Schmidt, Emily; Namusoke, Hanifa; Temple, Victor J.; Codling, Karen; Rudert, Christiane; Holtemeyer, Brian; Benson, Todd (International Food Policy Research Institute, 2019)
Dietary iodine deficiency results in stunted physical and mental growth in children. Fortifying commercial household salt with a small but adequate amount of iodine is the principal strategy used globally to prevent iodine deficiency. However, there may be barriers to consuming adequately iodized salt for many rural households in Papua New Guinea (PNG). Using results from a rural household survey conducted in four areas of the country in 2018 that was administered to just over 1,000 households, two issues related to salt iodization in PNG are examined. First, only about 9 percent of survey households reported that they did not consume iodized table salt in the seven days prior to being interviewed for the survey. However, specific characteristics are associated with such households. They tend to be located in remote communities, are in the poorest 20 percent of survey households, have no members who received any formal education, and have experienced recent food insecurity. Particularly for remote households, ensuring that their members consume sufficient iodine will require going beyond salt iodization to use other approaches to iodine supplementation. Second, of the samples of salt obtained from the survey households, the iodine content of two-thirds fell within the PNG regulations, a reasonably encouraging finding. Only about 17 percent of the almost 800 samples obtained had inadequate iodine. However, when the salt samples were examined by brand, it was found that the brand most commonly consumed had the highest share of samples with inadequate iodine levels. Closer monitoring of the iodine content in table salt produced or imported into PNG and enforcement of salt iodization regulations is required.